Pengelolaan Portal Berita Online dalam Undang-Undang Nomor 40 Tahun 1999 tentang Pers - Thonthowi Jauhari (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2017)
The results of the study show that, firstly, Law Number 14 Year1999 regarding the Press is still firm enough to regulate a presscompany performing its functions, rights and obligations in Indonesia,in the management of online news portals, nothing distinguishes withother types of media, explicitly mentioned in the law are online mediaphrases or similar terms. Secondly, the Press Council as an institutionauthorized by law to improve the life of the press, issued the CyberMedia Coverage Guidelines, because the internet as a new medium hasits own peculiarities. To crack down on websites or online portals thatdo not comply with legislation, journalistic ethics, and Cyber MediaCoverage Guidelines, the Ministry of Information and Communicationsestablishes Negotiated Negative Internet Handling Forums (FPSIBN)through Decree of the Minister of Communication and Information No.290 of 2015.